Gelation of a combination of insect and pork proteins as affected by heating temperature and insect:meat ratio. (November 2020) - Scholliers, Jana; Steen, Liselot; Fraeye, Ilse
Graphical abstract: Highlights: Gelation of a combination of extracted insect and meat proteins was studied. During heating, meat proteins showed best gelling properties. Insect proteins formed a considerable amount of structure during cooling. Mixtures of insect and meat proteins showed lower gel strengths than pure samples. Some proteins, that aggregated in pure samples, did not aggregate in the mixtures. Abstract: In order to better understand structure formation in hybrid meat products containing insects, viscoelastic properties, protein aggregation and surface hydrophobicity of extracted insect and meat proteins in different insect:meat nitrogen ratios (100:0, 75:25, 50:50, 25:75 and 0:100) at different heating temperatures (from 20 to 80 °C) were studied. During heating, meat proteins showed best gelling properties. This was probably associated with the formation of hydrophobic interactions, as was confirmed by the strong increase in surface hydrophobicity of the meat proteins upon heating. Insect proteins, on the other hand, formed a considerable amount of additional structure during cooling, resulting in gels with high gel strength, although their gel stability was low. As for the mixtures of insect and meat proteins, they showed lower final gel strengths compared to the pure insect and meat protein samples. Furthermore, proteins with molecular weights of 230 and 16 kDa, that aggregated in the pure samples, did not aggregate in the mixtures. Although the mechanism of the latter effect remains to be elucidated, it probably explains the lower gel strength observed in the protein mixtures.